Strategic entrepreneurial behaviors: Construct and scale development - Anderson, Brian S.; Eshima, Yoshihiro; Hornsby, Jeffrey S. (Strategic Entrepreneurship Journal, 2019)
Research Summary Delineating between conservative and entrepreneurial firms to discern the causes, consequences, and benefits of entrepreneurial behavior is a key conversation in strategic entrepreneurship research. We introduce to this conversation a new construct, Strategic Entrepreneurship Behaviors, which we argue provides several theoretical and practical benefits to scholars exploring strategic entrepreneurship phenomenon. We develop and validate a measurement model for the Strategic Entrepreneurship Behaviors construct using a three‐study design in Japan and in the United States. To facilitate reproducibility and replication of our results, we posted all data, R code, and Supporting Information on the Open Science Framework website available at https://osf.io/rqw5u/ . Managerial Summary The driving question in strategic entrepreneurship research is the impact of an organization's entrepreneurial activity on its performance. Answering this and related questions requires careful measurement of entrepreneurial activity. Existing measures and scales served the field well, but to answer questions establishing causal relationships, we need new constructs and measures robust to causal research designs. We introduce a new construct and scale, Strategic Entrepreneurial Behaviors , to capture the firm's exploitation of new product‐market opportunities through the intended commercialization of its product innovations. We hope this new measure for a firm's entrepreneurial activity allows researchers to build more predictive theory, and to ask—and answer—new research questions that move the strategic entrepreneurship conversation forward.